The Effect of Free Cash Flow and Leverage on Earnings Quality: The Effect of Free Cash Flow and Leverage on Earnings Quality - Gede Sedana Wibawa Yasa; Ni Putu Rita Sintadevi (Universitas Islam Lamongan, 2023)
This study aims to examine the relationship between free cash flow and leverage on earnings quality, this research is a type of quantitative research using secondary data from the Indonesian stock exchange, based on the criteria obtained from 41 banking companies that meet the aspects as a research sample. Based on the results of multiple regression analysis, it was found that free cash flow had a significant positive effect on earnings quality in banking sector companies listed on the IDX. This study also shows that leverage has a negative and significant effect on earnings quality in banking sector companies listed on the IDX.